The association of thyroid disorders with abnormal uterine bleeding - Deshmukh, Prasad Yeshwant; Boricha, B. G.; Pandey, Ankita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Dysfunctional uterine bleeding is an abnormal bleeding from the uterus in absence of organic disease of genital tract and demonstrable extragenital cause. Thyroid dysfunction is marked by large number of menstrual aberrations. This study is aimed at detecting thyroid dysfunction in patients with provisional diagnosis of AUB and refers positive cases to physician for further evaluation. Methods: 100 cases of clinically diagnosed AUB were taken from Gynaecology OPD and inpatients of MGM hospital, Kalamboli. All patients from 19 to 45 age groups presenting as menorrhagia, acyclical metropathia, polymenorrhagia, metrorhhagia, oligomenorrhoea, polymenorrhoea and hypomenorrhoea were tested for their thyroid function by T3, T4, TSH estimations in their serum. Patients who had clinical signs and symptoms of thyroid disease, were on hormonal treatment, IUCD users, or had bleeding disorders were excluded from the study. Results: 30% of patients who were studied had thyroid dysfunction, of which 18% of patients had subclinical hypothyroidism, 9% of patients had hypothyroidism and only 3% of patients had hyperthyroidism. The commonest bleeding abnormalities in subclinical hypothyroid patients were polymenorrhaggia and menorrhaggia. Most of the hyperthyroid cases were oligomenorrhoeic. Conclusions: Both subclinical hypothyroid and profoundly hypothyroid cases together were the commonest thyroid dysfunction and menorrhagia was their commonest menstrual abnormality. So this study concludes that, biochemical evaluation of thyroid functioning should be made mandatory in all provisionally diagnosed cases of DUB to detect thyroid dysfunction.